Open Gluteus Medius Double-Row Repair With Acellular Allograft Augmentation - Bruno Capurro MD, PhD; Daniel J. Kaplan MD; Thomas W. Fenn BS; Reagan S. Chapman MD; Shane J. Nho MD, MS (SAGE Publishing, 2023)
Background: Gluteus medius tears are a common pathology affecting the lower extremity, predominantly in older female patients, and most often caused by chronic degenerative changes. Due to the associated morbidity with gluteus medius insufficiency, various surgical repair techniques are utilized, including open and endoscopic approaches, with equivalent biomechanical outcomes. Indications: Open gluteus medius double-row repair with acellular allograft augmentation is indicated for patients with massive, full thickness tears, full thickness tears with extensive retraction, degenerative tears, poor tissue quality, revision cases where tendon reduction to the footprint is challenging, and impaired hip abduction strength. The primary benefit of acellular allograft use is the provision of immediate structural strength to the repair construct. Technique Description: The patient is placed in the lateral decubitus position, and a direct lateral incision is made over the greater trochanter. The gluteus medius and/or minimus tendons are identified, mobilized, and provisionally reduced to the footprint. The tendon footprint is then debrided, and proximal anchors are placed. The graft is provisionally fixed to the tendon with sutures anteriorly and posteriorly to ensure correct placement. Sutures are passed from the proximal row through the tendon and prepared allograft, where 1 suture limb from each mattress is placed into a double-row anchor in the distal row. Once secured, the repair is checked through a range of dynamic positions. Results: Although outcomes studies are limited, case series of patients undergoing open gluteus medius repair with allograft have demonstrated favorable patient-reported outcomes, improved pain, improved hip abduction strength, and improved gait. Discussion: Open gluteus medius repair with acellular allograft provides immediate structural strength to the repair construct and should be considered in patients with massive, full thickness tears with extensive retraction, degenerative tears with poor tissue quality, revision cases, and impaired hip abduction strength. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.